Cities and regions in transition - Roberta Capello; Andrea Conte (FrancoAngeli, 2023)
The conference of the Italian Regional Science Association (AISRe), held in September 2022 in Milan, provided a great opportunity to reflect on the local responses to the important challenges that European territories are facing. This book collects a series of contribution that were presented during the conference, with a main focus on local and regional economic systems. Far from being exhaustive on the issue of global challenges and local responses, it highlights some of the ways in which cities and regions are grappling with the transformative processes imposed by disruptive challenges, such as shifts in labour markets and working conditions, the increasing urgency of environmental concerns and the push for resource-efficiency and decarbonisation, and the drive to increase productivity and growth through modernisation processes, irrespective of the type of sectoral specialization (high vs. low sectors). The book is structured in three parts. The first part presents four papers dealing with the recent challenges and the regional responses to such challenges. The second part of the book is dedicated to novel methods and applications for spatially monitoring and analysing socio-economic transformations, focusing in particular on R&I investments, value chains, poverty, wellbeing and firms' efficiency levels. The third part of the book focuses on the role of cohesion policies in guiding socio-economic transformations.
Keywords: 330